Analysis of Heat Transfer in Cocoa Bean Fermentation Chamber (Theobroma cacao L.) Using Different Types of Fermentation Containers - Wiantara, I Wayan Satrio; Yulianti, Ni Luh; Setiyo, Yohanes (Jurnal BETA (Biosistem dan Teknik Pertanian), 2022)
Fermentation is one a process that plays an important role in improving the quality of cacao beans produced, the indicator of the fermentation process proceed well is temperature increase in thefermenter caused by microorganism activity. The purpose of this research is to test and discover temperature distribution, heat transfer, and cacao bean quality with a different type of fermentation container. The material used is bulk cacao beans which are obtained from Pupuan village farmer, Pupuan subdistrict, Tabanan regency. The fermentor is in the form of bamboo boxes, styrofoam boxes, and wooden boxes with dimensions of 23.5 cm x 23.5 cm x 29.5 cm with a capacity of 9.5 kg. The type of fermentor boxes is the treatment of this research. Fermentation was carried out for 144 hours and observed every 6 hours at 5 point temperature measurement that is on the pile of cocoa beans, inner material wall of the fermentor, outer material wall of the fermentor, wall temperature of fermentor structure, and surrounding temperature. Parameter observed in this research among others is the fermentation temperature of wet cocoa beans, heat transfer analysis that occurs during the fermentation process, the water contentof dry cocoa beans, and amount of beans per 100 gram. Research results indicate peak temperature of fermentation on bamboo fermentor, styrofoam, and wood reaching peak respectively with temperature 44,5ºC, 43,1ºC dan 43,2ºC at 60,66,78 hours. From the parameter observed bamboo fermentor constitutes the best treatment with a peak temperature of fermentation reaching 44,5°C to water content parameter as much as 7,48 % and amount of beans per 100 gram in the amount of 73 beans that have met the standard SNI 2323:2008.